The Role of Strategic Ambidexterity in Achieving Organizational Sustainability: An Exploratory Study of the Opinions of a Sample of Administrative and Academic Leaders in Private Universities in The Kurdistan Region of Iraq. (Raparin Journal of Humanities (RJH), 2025)
This research aims to analyze the relationship and impact between strategic ambidexterity in its dimensions (exploratory strategy, exploitative strategy, and structural flexibility) and organizational sustainability, represented by (economic sustainability, social sustainability, environmental sustainability, and ethical sustainability) in private universities in the Kurdistan Region of Iraq. After reviewing a group of studies and literature, theoretical concepts were written and a model and hypotheses were built based on the dimensions of strategic ambidexterity and organizational sustainability, and based on the nature of the research and the goals it seeks to achieve, reliance was placed on the descriptive and analytical approach. In order to collect data, a questionnaire form was relied upon, and (289) questionnaires were distributed directly to all members of population, represented by deans, their assistants, and heads of departments and units in private universities in the Kurdistan Region of Iraq (289) individuals. (256) questionnaires were retrieved, and after sorting and checking the received questionnaires, the number of questionnaires suitable for analysis reached (242). Several statistical methods were used, including arbitrators and Cronbach's alpha to ensure validity and reliability, factor analysis, numerator correlation, and structural equation modeling using (SPSS-26) and (AMOS-26) programs. The results showed that there is a positive correlation and impact between the research variables and its dimensions. Based on the results of the research, a number of recommendations were presented related to the need for administrations, leaders, and private universities to focus on adopting strategic ambidexterity in order to achieve organizational sustainability for the researched universities.